The Deepening Crisis as an Accelerator of Withdrawal From the Public Sphere or an Activator of Civic Engagement? - Kwiecińska-Zdrenka, Monika (Roczniki Nauk Społecznych, 2023)
The subject of the article is whether facing the crisis (crises) and the accompanying individual experience of anxiety may lead to further withdrawal of young people from the public sphere (deepening indifferentism and civic helplessness), or, on the contrary, it may serve as a kind of trigger for the dormant civic potential of young people (about as long as they have appropriate civic competences) or the emergence of new citizen-state, citizen-social problems relations. The second question we pose here is whether Poles brought up and socialized in different political contexts (young adults – approx. 35 years old – and their parents aged approx. 60) can launch different strategies in the face of these new challenges. We seek answers to these questions based on empirical material from a longitudinal study in Toruń covering two generations (people born in 1958 and 1983 – the older generation has been surveyed several times since 1973).